Nasal function and CPAP compliance. Issue 4 (August 2019) - Inoue, Akiko; Chiba, Shintaro; Matsuura, Kentaro; Osafune, Hiroshi; Capasso, Robson; Wada, Kota
Abstract: Objective: Continuous positive airway pressure (CPAP) is the mainstay therapy for patients with obstructive sleep apnea (OSA) however compliance with CPAP is variable. Nasal ailments, such as nasal congestion are frequently mentioned as a cause for CPAP non-compliance, and potentially could be addressed prior to CPAP initiation, however, no specific criteria or recommendations for the evaluation and management of these patients exist. The aim of this retrospective study is to evaluate the effects of nasal anatomic features and disease on adherence to CPAP therapy for patients with OSA and determine the indications for pre-CPAP nasal treatment by using data obtained at clinical examination. Methods: In total, 711 adult patients with initial diagnosis of OSA and an apnea–hypopnea index of ≥20 who were amenable to CPAP were included. We analyzed nasal parameters, past history of nasal disease, subjective symptoms, and disease severity in addition to whether CPAP therapy had been initiated, rate of CPAP therapy use (initial and 1 year), treatment continuation rate at 2 months and 1 year, and nasal treatments for all patients. Results: CPAP therapy was initiated in 543 of 711 patients. Nasal resistance was significantly higher in patients who discontinued therapy soon after CPAP initiation. Nasal disease and nasal parameters were not found to be predictors of treatment adherence at 1 year. Allergic rhinitis, moderate to severe nasal congestion at bedtime, slight or extensive sinus opacification, and a high nasal septum deviation score were found to be independent predictors of nasal treatment, while strong awareness of nasal congestion, a past history of sinusitis, and a total nasal resistance (supine position) of ≥0.35 Pa/cm 3 /s were independent predictors of surgical treatment. Conclusion: Long-term CPAP therapy adherence in patients with OSA can be predicted from initial CPAP adherence. Nasal disease and nasal parameters are important factors for early CPAP therapy discontinuation and should be adequately treated before therapy initiation to ensure long-term adherence. Indications for pre-CPAP nasal treatment and nasal surgery for patients with OSA can be predicted from the data obtained at the first examination, and these patients should be treated differently from those without OSA.